Health insurance acceptance of female labour force: a special focus on reproductive health - Mohammad Aman Ullah; Sobia Rose; Asima Ihsan; Bushra Fatima; Gulalai Khan (Journal of the Pakistan Medical Association, 2021)
Objective: Maternal health insurance is recognized as a useful tool to manage healthcare risks in many countries of the world. Given the importance of the maternal health insurance, this study is an initial exercise to measure the demand for health insurance policy with special focus on maternity services among working women. Methods: The target population was public and private school teachers of reproductive age. The primary data was collected in Lahore using a structured questionnaire. Logit model was used to determine the factors affecting the interest in maternal health insurance. Results: The findings suggest that 57 percent of the respondents are willing to buy maternal health insurance with maximum average willingness to pay of Rs. 1060 ($8.2) per month as a premium, which is on average 3.56 percent of their income. The results show that income, age and awareness are some of the important determinants of willingness to pay for maternal health insurance. Conclusion: Providing full insurance coverage at the time of maternity will give financial relief and will also ensure better health conditions of the teachers after rejoining the work. Continuous....